ANALISIS GREEN PURCHASE INTENTION YANG DIMEDIASIGREEN TRUST PADA PRODUK REFILL STATION PT UNILEVER INDONESIA TBK - Siti Rizky Isnaini (2023)
This study aims to demonstrate the influence of Green Perceived Value and Environmental Knowledge on Green Purchase Intention, mediated by Green Trust, regarding the products of Refill Station PT Unilever Indonesia Tbk. The study employs a quantitative method by distributing questionnaires to 151 respondents located in Jabodetabek, aged above 17 years old, and familiar with the products of Refill Station PT Unilever Indonesia Tbk. Data collection utilized purposive sampling technique and was analyzed using descriptive and inferential analysis techniques with the Partial Least Square (PLS) method, supported by SmartPLS software version 3.2. The results of the data analysis indicate that: (1) Green Perceived Value has an impact on Green Purchase Intention; (2) Environmental Knowledge has an impact on Green Purchase Intention; (3) Green Trust has an impact on Green Purchase Intention; (4) Green Perceived Value has an impact on Green Purchase Intention through Green Trust; and (5) Environmental Knowledge has an impact on Green Purchase Intention through Green Trust.